A Neurotoxic Ménage-à-trois: Glutamate, Calcium, and Zinc in the Excitotoxic Cascade - Granzotto, Alberto; Canzoniero, Lorella M. T.; Sensi, Stefano L. (Frontiers in Molecular Neuroscience, 2020)
Fifty years ago, the seminal work by John Olney provided the first evidence of the neurotoxic properties of the excitatory neurotransmitter glutamate. A process hereafter termed excitotoxicity. Since then, glutamate-driven neuronal death has been linked to several acute and chronic neurological conditions, like stroke, traumatic brain injury, Alzheimer's, Parkinson's and Huntington's diseases, and Amyotrophic Lateral Sclerosis. Mechanisms linked to the overactivation of glutamatergic receptors involve an aberrant cation influx, which produces the failure of the ionic neuronal milieu. In this context, zinc, the second most abundant metal ion in the brain, is a key but still somehow underappreciated player of the excitotoxic cascade. Zinc is an essential element for neuronal functioning, but when dysregulated acts as a potent neurotoxin. In this review, we discuss the ionic changes and downstream effects involved in the glutamate-driven neuronal loss, with a focus on the role exerted by zinc. Finally, we summarize our work on the fascinating distinct properties of NADPH-diaphorase neurons. This neuronal subpopulation is spared from excitotoxic insults and represents a powerful tool to understand mechanisms of resilience against excitotoxic processes.